Senam bugar lansia berpengaruh terhadap daya tahan jantung paru, status gizi, dan tekanan darah - Sri Thristyaningsih; Probosuseno Probosuseno; Herni Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Aging that happens naturally in human life does not only cause physical dysfunction but also have an impact to mental and social aspects. In the elderly there is a problem of degenerative disease. Hypertension has become a serious health problem and a major challenge of public health worldwide because of either high prevalence or major risk factor for cardiovascular disease. Pharmacological as well as non-pharmacological efforts have been made to prevent and cure the disease; however until today the growing number of hypertensive patients has not been successfully controlled. Consequently behavioral intervention has to be made to cure hypertensive patients. One of the recommended interventions is fitness exercise for the elderly.Objective: The study aimed to identify the effect of fitness exercise to increasing stamina of heart and lung, nutrition status and reduced blood pressure of hypertensive elderly at integrated service post of Sub district of Pahandut, Palangkaraya Municipality.Method: The study was an experiment (before and after) without control group using one group pretest posttest study design. Subject of the study was a group with pre experimental, evaluation, effect of variables and post experimental evaluation. Measurement was made in week two, three and four to blood pressure, heart and lung stamina, nutrition status of hypertensive elderly, discipline in exercise and food recall 24 hours. The interventions made were lecture and fitness exercise package D for the elderly.Results: There was significant association between elderly fitness exercise and systolic blood pressure, heart and lung stamina and nutrition status of hypertensive elderly (p<0.05). Result of Wilcoxon signed ranks test and paired sample test between gymnastic elderly on increase of endure capacity heart lung are significantly associated (p=0,001) and so on nutritional status (p=0,002) and decrease systolic tension (p=0,001) and diastolic tension (p=0,002).Conclusion: There was significant association between elderly fitness exercise and the increase of heart and lung stamina, nutrition status and the decrease of blood pressure in hypertensive elderly.